Teaching Quality Evaluation in Mathematics Courses Using Relative Important Index: A Case Study in Neijiang Normal University - Ya Qin; Siti Rahayu Mohd. Hashim; Jumat Sulaiman (Faculty of Science & Natural Resources, UMS, 2022)
Classroom teaching evaluation is an important part of teaching. The key of evaluation is to choose an appropriate evaluating instrument and assign reasonable weight to its evaluation indices. This study choose a classroom observation instrument “Reformed Teaching Observation Protocol (RTOP)” as an evaluating tool to measure the relative importance of factors in RTOP in mathematical courses. To achieve this goal, relative important index (RII) technique is used to determine the values of relative importance among items. The items are ranked according to the RII values. The sample of this study consists of 30 selected mathematics teachers and students. The analysis results showed that all RII values are greater than 0.5, which indicates that items are at Medium to High levels of importance. Furthermore, the ranking results also showed the factor “Lesson design and implementation” ranked first, followed by “Propositional pedagogic knowledge” and “Procedural pedagogic knowledge”, while the factor “Communicative interactions” ranked last. The findings showed that lesson design as well as implementation is the most important factor in ensuring the teaching quality of mathematical courses amongst the respondents.